Analisis Pengaruh Struktur Modal Terhadap Pajak Penghasilan Badan Terutang Pada Perusahaan Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021 – 2023 - Gilvitan, Shinta (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the effect of capital structure on corporate income tax payable in companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange during the period 2021–2023. Capital structure is measured using four indicators: Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long-term Debt to Asset Ratio (LDAR), and Long-term Debt to Equity Ratio (LDER). The research sample consists of 24 companies over a three-year period, resulting in 72 firm-year observations. Corporate income tax payable is used as the dependent variable. This research employs a quantitative associative method with a causal approach and multiple linear regression analysis. The data used are secondary data obtained from companies’ annual reports. The results indicate that partially, the Debt to Asset Ratio (DAR) has no significant effect on corporate income tax payable. Meanwhile, the Debt to Equity Ratio (DER) and Long-term Debt to Equity Ratio (LDER) have a negative and significant effect. In contrast, the Long-term Debt to Asset Ratio (LDAR) has a positive and significant effect. Simultaneously, the four independent variables have a significant effect on corporate income tax payable. These findings suggest that decisions regarding capital structure—particularly the composition of debt and equity—play an important role in determining the company’s tax obligations.